2011
DOI: 10.1007/s13361-010-0033-4
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Metabolome Analysis of Human Cerebrospinal Fluid by13C-/12C-Isotope Dansylation Labeling Combined with Liquid Chromatography Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: Metabolome analysis of human cerebrospinal fluid (CSF) is challenging because of low abundance of metabolites present in a small volume of sample. We describe and apply a sensitive isotope labeling LC-MS technique for qualitative analysis of the CSF metabolome. After a CSF sample is divided into two aliquots, they are labeled by 13 C-dansyl and 12 C-dansyl chloride, respectively. The differentially labeled aliquots are then mixed and subjected to LC-MS using Fourier-transform ion cyclotron resonance mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…25, 26 Stable isotope labeling can be categorized into two groups, mass-difference labeling and isobaric labeling. Mass-difference labeling, such as 12 C-/ 13 C-methyl acetimidate, 27 dansylation, 28, 29 and formaldehyde dimethylation, 30 introduces a fixed mass difference for the same metabolite in a MS spectrum. Relative quantification is achieved by comparing extracted ion chromatogram peak areas of the heavy and light isotopic forms of the same metabolite.…”
Section: Introductionmentioning
confidence: 99%
“…25, 26 Stable isotope labeling can be categorized into two groups, mass-difference labeling and isobaric labeling. Mass-difference labeling, such as 12 C-/ 13 C-methyl acetimidate, 27 dansylation, 28, 29 and formaldehyde dimethylation, 30 introduces a fixed mass difference for the same metabolite in a MS spectrum. Relative quantification is achieved by comparing extracted ion chromatogram peak areas of the heavy and light isotopic forms of the same metabolite.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Guo and Li developed a CIL method based on 12 C 2 -and 13 C 2 -dansyl chloride (DnsCl) [1]. Although the method allows for rapid and accurate quantification of amine-containing metabolites [26][27][28][29], metabolite identification, particularly for unknown metabolites, is a challenge due to the lack of structural information in the MS/MS spectra of dansyl labeled metabolites. Tsukamoto et al developed H 6 -/D 6 -7-(N,Ndimethylaminosulfonyl)-4-(aminoethyl)-piperazino-2,1,3-benzoxadiazole (H 6 -/D 6 -DBD-PZ-NH 2 ) to profile fatty acids in rat plasma samples [8] and Shimbo et al reported the use of p-N,N, N-trimethylammonioanilyl N 0 -hydroxysuccinimidyl carbamate iodide (TAHS) and D 3 -TAHS for amino acid quantification [30].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of internal standardization methods using isotope labeled compounds ( 2 H, 13 C, 15 N) as well as external standardization methods are also available to provide much better reproducibility. First developed to provide improved quantitation in the field of proteomics, the use of mixtures of metabolites containing light and heavy isotopes is a popular method for relative and absolute quantitation of metabolites using MS methods [4750]. Targeted methods that use such internal standards compensate ion-suppression effects and provide reliable metabolite quantitation.…”
Section: Global and Targeted Metabolic Profilingmentioning
confidence: 99%